Retrieval of a fractured tooth fragment embedded in the lower lip - Vijayakumar Rajendran; Selvakumar Haridoss; Ganesh Rajendran; Hemalatha Ramkumar (Wolters Kluwer Medknow Publications, 2013)
Traumatic injuries to the maxillary anterior teeth due to domestic accidents and contact sports leading to tooth fracture are a common finding in a pedodontic practice. Sometimes the fractured tooth fragment can penetrate into the surrounding soft-tissue and may be often missed in a routine clinical examination. This case report presents a 10-year-old boy who reported to the Department of Pedodontics, SRM Dental College with fractured maxillary right central incisors along with lower lip laceration due to trauma. Patient was subsequently diagnosed with a fragment of a fractured permanent central incisor in the lower lip after routine clinical examination and radiographic examination. Patient was initially seen at a private dental hospital, where the embedded dental fragment in the lower lip went unnoticed. The fragment was removed surgically and composite filing was done in the fractured central incisor at a later stage. This report highlights the importance of thorough clinical examination followed by radiographic examination in patients reporting with dental fractures due to trauma.